Parametric insurance solutions - is it a legally viable option as the midpoint between traditional insurance and index-based derivatives from a South African perspective? - Grove, N.J. (University of Pretoria, 2023)
Dissertation (LLM (Insurance Law and Governance))--University of Pretoria, 2022.